Proposta de framework para implementação de inteligência artificial no segmento médias empresas de banco público brasileiro - Silveira, Eduardo Estima da (Universidade do Vale do Rio dos Sinos, 2023)
The use of artificial intelligence (AI) in the organizational environment has been disseminating and presents opportunities and threats to organizations. The banking sector is considered intensive in the adoption of AI techniques. On the other hand, public organizations have faced difficulties in keeping up with technological innovations at the same pace as private organizations. This study investigates the implementation of AI in the medium-sized companies segment of a Brazilian public bank, aiming to propose an artifact, referred to as a framework, to guide the adoption of AI in the researched context. The design science research method was employed for the proposition, development, and evaluation of the framework. The proposed artifact consolidates elements identified through bibliographic research, participant observation, documentary research, and semi-structured interviews. The developed framework presents three stages for AI implementation: prepare, pilot, and scale. Critical factors associated with each of these stages deserve attention from managers for the proper implementation of AI. The mentioned factors include: data, support, governance, people, awareness, collaboration, partnerships, risks, biases, use case, project definitions, human-in-the-loop, monitoring, optimization, knowledge transfer, and transparency.
Keywords: Inteligência artificial; Implementação; Setor bancário; Setor público; Artificial intelligence; implementation; Banking sector; Public sector; ACCNPQ::Ciências Sociais Aplicadas::Administração